Crystal structures and circular dichroism of {2,2′-[(1S,2S)-1,2-diphenylethane-1,2-diylbis(nitrilophenylmethanylylidene)]diphenolato}nickel(II) and its ethanol solvate - Masataka Ito; Noriko Chikaraishi Kasuga; Ryo Matsuse; Masakazu Hirotsu (Acta Crystallographica Section E: Crystallographic Communications)
The title compound, [Ni(C40H30N2O2)] (1), with an optically active Schiff base ligand derived from 2-hydroxybenzophenone and (1S,2S)-1,2-diphenylethylenediamine, was crystallized as the solvent-free and ethanol solvate forms (1 and 1·2C2H5OH). In both structures, the two phenyl groups on the stereogenic centers of the O,N,N,O-tetradentate ligand are axially oriented, and the conformation of the central diamine chelate ring is λ. The circular dichroism (CD) spectra of 1 and the analogous nickel(II) complex [Ni(C30H26N2O2)] (2) in solution show partially similar patterns in the 350–450 nm range, but are mirror images in the longer wavelength region (450–650 nm). In the latter region, the sign of CD for these complexes is sensitive to the substituents on the C=N carbon atoms (phenyl for 1 and methyl for 2) rather than the diamine chelate ring conformation.